2019
DOI: 10.3168/jds.2018-15826
|View full text |Cite
|
Sign up to set email alerts
|

Rumen microbial responses to supplemental nitrate. II. Potential interactions with live yeast culture on the prokaryotic community and methanogenesis in continuous culture

Abstract: Nitrates have been fed to ruminants, including dairy cows, as an electron sink to mitigate CH 4 emissions. In the NO 3 − reduction process, NO 2 − can accumulate, which could directly inhibit methanogens and possibly other microbes in the rumen. Saccharomyces cerevisiae yeast was hypothesized to decrease NO 2 − through direct reduction or indirectly by stimulating the bacterium Selenomonas ruminantium, which is among the ruminal bacteria most well characterized to reduce both NO 3 − and NO 2 −. Ruminal fluid w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 57 publications
(87 reference statements)
5
27
0
Order By: Relevance
“…Yeast cultures in the feed ration do not affect the prevalence of lameness in cows, but have the effect of reducing the locomotion score [ 29 ]. Yeast culture, especially Saccharomyces cerevisiae, often improves digestibility of neutral detergent fiber [ 138 , 139 ] could increase acetate, but also increase the production of dry matter intake and milk. Yeast increases the availability of dicarboxylic acids, which perform central metabolic reactions and serve as electron carriers [ 138 ].…”
Section: Effect Of Nutrition On Lameness and Laminitismentioning
confidence: 99%
“…Yeast cultures in the feed ration do not affect the prevalence of lameness in cows, but have the effect of reducing the locomotion score [ 29 ]. Yeast culture, especially Saccharomyces cerevisiae, often improves digestibility of neutral detergent fiber [ 138 , 139 ] could increase acetate, but also increase the production of dry matter intake and milk. Yeast increases the availability of dicarboxylic acids, which perform central metabolic reactions and serve as electron carriers [ 138 ].…”
Section: Effect Of Nutrition On Lameness and Laminitismentioning
confidence: 99%
“…Rather than strategies to inhibit H 2 production to suppress methanogenesis, alternative electron receptors such as NO 3 − salts have been added so that NO 3 − -reducing bacteria compete with methano-6145 gens for aqueous H 2 (Morgavi et al, 2010). Therefore, our aim was to assess whether dietary NO 3 − salts would mitigate methanogenesis while potentially shifting fermentation pathways and bacterial populations, as we detected in continuous culture (Welty et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Such variability might be a result of sequencing approaches compared with quantitative PCR (Jiang et al, 2017). However, protozoa and uncharacterized bacteria other than S. ruminantium appear to have important roles in NO 3 − and NO 2 − reduction (Yang et al, 2016), and protozoa appear to reduce NO 3 − but also are inhibited by NO 2 − (Roman-Garcia et al, 2019). In a previous study, Welty et al (2019) suggested that live yeast culture (LYC) could help mediate NO 2 − accumulation in continuous cultures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the growing interest of agricultural microbiomes and their responses to different agricultural management systems, the focus has been usually within speci c niches, such as soil [61,62], rumen [63,64], or rhizosphere [28,65]. However, microbial interactions also play a critical role in many ecosystem process, especially nutrient cycling [66], that may have carry over effects into other niches.…”
Section: Discussionmentioning
confidence: 99%